The effect of different OvaprimTM dosage for artificial spawning and reproductive performance of jelawat fish (Leptobarbus hoevenii) - Muhammad Sugihartono; Eko Harianto; Muhammad Yusuf Arifin; Safratilofa Safratilofaa; Dedi Pardiansyah; Dwinda Pangentasari; Fadly Al Adha (Universitas Malikussaleh, 2026)
The availability of quality jelawat fish seeds as input for enlargement activities is still experiencing problems, especially continuity. One way to improve the availability of high-quality seeds are through the application of artificial spawning using the hormone Ovaprim. The purpose of this study was to determine the optimal dose of the Ovaprim hormone for artificial spawning and the reproductive performance of jelawat fish (Leptobarbus hoevenii). The study was conducted for three months, from April to June 2024, at the Telanaipura Ornamental Fish Facility of the Jambi Provincial Department of Marine Affairs and Fisheries. This study employed a completely randomised design with four treatments and three replicates. The treatments used were ovaprim dose of 0.3 ml/kg (P1), ovaprim dose of 0.5 ml/kg (P2), ovaprim dose of 0.7 ml/kg (P3) and ovaprim dose of 0.9 ml/kg (P4). The test parameters included latency time, fecundity, egg diameter, fertilization rate and hatching rate. The results showed that the shortest latency time was observed in treatment P4, at 2.67 hours, whilst the longest latency time occurred in treatment P1, at 13.67 hours. Fecundity values ranged from 23.767 to 28.338 eggs. Egg diameter ranged from 0.70 to 0.82 mm. The highest fertilization rate was observed in treatment P3 at 84.04%, whilst the lowest fertilization rate was observed in treatment P1 at 45%. The highest hatching rate was observed in treatment P3 at 84.97%, whilst the lowest hatching rate was observed in treatment P1 at 28.00 %. This study found that a dose of 0.7 ml/kg of the hormone ovaprim was the most effective, yielding the highest fertilisation and hatching rates compared to the other treatments. Keywords: Hormonal; Jelawat fish; Ovaprim; Spawning